Assessment of water balance approach for different water supply conditions in Dahuk Dam - Solaiman, Maher Hussain, 1977-; Arien Heryansyah; Fakulti Kejuruteraan Awam (2013)
Thesis (Sarjana Kejuruteraan (Awam - Hidraul dan Hidrologi)) - Universiti Teknologi Malaysia, 2013